2003
DOI: 10.1523/jneurosci.23-25-08752.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Inhibitory Pathway between Substantia Gelatinosa Neurons Receiving Direct C-Fiber Input

Abstract: The spinal substantia gelatinosa (SG) is a major termination region for unmyelinated (C) primary afferent fibers; however, how the input it receives from these sensory fibers is processed by SG neurons remains primarily a matter of conjecture. To gain insight on connections and functional interactions between intrinsic SG neurons, simultaneous tight-seal, whole-cell recordings were made from pairs of neurons in rat spinal cord slices to examine whether impulses in one cell generated synaptic activity in the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
310
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(349 citation statements)
references
References 35 publications
37
310
2
Order By: Relevance
“…The authors identified a monosynaptic inhibitory connection between two different types of neuron located within the mid portion of the spinal substantia gelatinosa. The fact that the presynaptic cell in the pairs consistently showed lower thresholds and slower dorsal root evoked excitatory post synaptic potentials (EPSPs) than the postsynaptic neuron was consistent with the notion that the dorsal root excitation was associated with relatively large diameter rapidly conducting C-LTMs while the postsynaptic cell was in receipt of c-nociceptive inputs (Lu and Perl, 2003). Further support for the notion that C-LTM inputs can supress nociceptive impulses comes from the observation that administration of TAFA4, a chemokine protein and specific marker on C-LTMs, reduced inflammation induced mechanical hypersensitivity (Delfini et al, 2013).…”
Section: C-tactile Afferents Inhibit Painsupporting
confidence: 69%
See 1 more Smart Citation
“…The authors identified a monosynaptic inhibitory connection between two different types of neuron located within the mid portion of the spinal substantia gelatinosa. The fact that the presynaptic cell in the pairs consistently showed lower thresholds and slower dorsal root evoked excitatory post synaptic potentials (EPSPs) than the postsynaptic neuron was consistent with the notion that the dorsal root excitation was associated with relatively large diameter rapidly conducting C-LTMs while the postsynaptic cell was in receipt of c-nociceptive inputs (Lu and Perl, 2003). Further support for the notion that C-LTM inputs can supress nociceptive impulses comes from the observation that administration of TAFA4, a chemokine protein and specific marker on C-LTMs, reduced inflammation induced mechanical hypersensitivity (Delfini et al, 2013).…”
Section: C-tactile Afferents Inhibit Painsupporting
confidence: 69%
“…While the tactile stimulus delivered in this study was optimised for activation of discriminative Aβ afferents, several recent animal studies have indicated specific activation of CLTMs also has analgesic effects. For example, Lu and Perl (2003) using whole cell recording in rat spinal cord slices provided evidence of a role for CLTMs in inhibiting c-nociceptive inputs to the dorsal horn. The authors identified a monosynaptic inhibitory connection between two different types of neuron located within the mid portion of the spinal substantia gelatinosa.…”
Section: C-tactile Afferents Inhibit Painmentioning
confidence: 99%
“…The latter apparently contradicts previous studies arguing that loss of inhibitory control at lamina II may lead to abnormal pain sensations (Meisner et al, 2010;Takazawa and MacDermott, 2010b). However, it can be seen from Figure 1 that inhibition of the I-Neuroid (which represents the islet cell reported by Lu and Perl (2003)) "disinhibits" the IC-Neuroid (the inhibitory central cell reported by Zheng et al (2010)), which in turn inhibits the afferent input from the Aδ-Neuroid to the vertical cell-Neuroid (V-Neuroid), thereby resulting in a diminished response of the P-Neuroid. It suggests that reciprocal inhibitory linkages at lamina II may regulate not only cross-modal interactions between inputs from different subpopulations of primary afferents, but also the proper level of pain sensitivity by a very fine tuning mechanism.…”
Section: Regionally Specific Subpopulations Of Sdh Neurons May Prevencontrasting
confidence: 56%
“…Lu and co-workers identified an inhibitory (Lu and Perl, 2003), an excitatory (Lu and Perl, 2005) and a normally silent pathway (Lu et al, 2013) by performing "paired" patch clamp recordings on SDH neurons in a slice preparation. Zheng et al (2010) reported the presence of a subset of inhibitory central cells which interact reciprocally with islet cells in transgenic mice where the green fluorescent protein (GFP) gene was inserted, such that the GFP expression was restricted to that subpopulation of neurons (Tamamaki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, substantial numbers of SG neurons respond well to light tactile stimuli, whether touch-specific or wide dynamic range neurons Bennett et al, 1980) (for review, see Light, 1992). Historically, while inhibition of nociceptive transmission by tactile inputs has received the most attention (Melzack and Wall, 1965) [see also Narikawa et al (2000) and Lu and Perl (2003)], recent studies suggest that most SG circuits are excitatory (Lu and Perl, 2005;Santos et al, 2007) and that incoming sensory information is relayed to neurons outside the SG (Giesler et al, 1978;Willis et al, 1978;Light, 1992;Eckert et al, 2003).…”
Section: Substantia Gelatinosa: Pleasure or Pain?mentioning
confidence: 99%